Surface evaluation of titanium oxynitride coatings used for developing layered cardiovascular stents; Materials Science and Engineering: C; Vol. 99 - Beshchasna N. Nataliia; Baumbach T. Tilo; Ho Au Yeung Kwan; Kraskiewicz H. Honorata; Wasyluk L. Lukasz; Kuzmin O. Oleg; Duta O. C. Oana Cristina; Ficai D. Denisa; Trusca R. D. Roxana Doina; Ficai A. Anton; Pichugin V. F. Vladimir Fyodorovich; Opitz J. Jorg; et al. (2019, 2019)
Title screen